Permeability and hydraulic conductivity of faulted micaschist in the eastern Elba Island exhumed geothermal system (Tyrrhenian sea, Italy): insights from Cala Stagnone. (November 2017) - Zucchi, Martina; Brogi, Andrea; Liotta, Domenico; Rimondi, Valentina; Ruggieri, Giovanni; Montegrossi, Giordano; Caggianelli, Alfredo; Dini, Andrea
Highlights: Geometrical parameters of veins and mineralized cataclasites have been used to calculate the secondary permeability of damaged volumes. The analysis of an exhumed geothermal system provided data on the hydraulic parameters of the palaeo-reservoir. The fracture network related to superposed faults has been reconstructed for micaschist hosting a magmatic intrusion. Fluid inclusions analyses given data on temperature and salinity of magmatic fluids feeding the palaeo-geothermal system. Abstract: Estimating values of permeability (k), efficient porosity (P) and hydraulic conductivity (K) by analysing field outcrops as analogue of geothermal reservoirs, is a timely theme useful for predictions during geothermal exploration programs. In this paper we present a methodology providing k, P and K values, based on geometric analysis of quartz-tourmaline faults-vein arrays hosted in micaschist exposed in south-eastern Elba Island (Tuscan Archipelago, Italy), considered as the analogue of rock hosting the so-called "deep reservoir" in the Larderello geothermal field. The methodology is based on the integration among structural geology, fluid inclusions results and numerical analyses. Through a detailed structural mapping, scan lines and scan boxes analyses, we have reconstructed three superposed faulting events, developed in an extensional setting and framed in the Neogene evolution of inner Northern Apennines. Geometrical data of the fault-veins array were processed by reviewing the basic parallel-plate model equation for k evaluation. Fluid inclusion analyses provided those salinity and pressure-temperature values necessary for defining density and viscosity of the parent geothermal fluids. Then, permeability, density and viscosity were joined to get hydraulic conductivity (K). Permeability is estimated between 5 × 10 −13 and 5 × 10 −17 m 2 with variations among the different faults generation, while the hydraulic conductivity is encompassed between 1.31 × 10 −8 and 2.4 × 10 −13 m/s. The obtained permeability and hydraulic conductivity values are comparable with those from several geothermal areas, and in particular from the Larderello geothermal field. The main conclusion is that the proposed integrated approach provides a reliable methodology to obtain crucial values, normally obtained after drilling, for developing numerical flow models of geothermal fluid path in active geothermal systems by field and laboratory analyses of analogue, exhumed, geothermal systems.